Evaluation of the characterization of thrombi in vitro by optical coherence tomography. (1st October 2016) - Yang, Guang; Zhang, Xiaoyuan; Meng, Qingyang; Ma, Dan; Yu, Huai; Ren, Xuefeng; Lv, Bo; Zhang, Shaosong; Yang, Shuang; Yu, Bo
Abstract: Aim: The purpose of this study was to provide a new assessable method of the optical coherence tomography (OCT) in characterization of thrombi with different concentrations of red blood cell (RBC). Methods and results: A series of thrombus models were constructed by using human blood in vitro. The thrombi were made by using human blood with different concentration of RBC (from 1% to 35%). Then tip of an FD-OCT catheter was put on the top of the thrombus to scan. After OCT being performed, all the acquired images were processed by a newly developed software to analyze the RBC levels related thrombus characteristics including attenuation, backscattering and light penetration depth. The attenuation was correlated with RBC concentration up to 9%. However, no apparent change was observed in thrombus with RBC concentration range from 10% to 35%. The same trend was seen in backscattering and penetration depth. Conclusions: FD-OCT is able to detect thrombus with different RBC concentrations up to 9%.